The use of a thoracodorsal flap in the surgical treatment of squamous cell skin cancer (case report) - Т. V. Zakharkina; E. P. Kulikov; A. I. Nurieva; M. B. Zaitsev; T. Ch. Allakhyarov; A. V. Grigoriev (Сибирский онкологический журнал)
We report a case of successful surgical treatment of a patient with locally advanced cutaneous squamous cell cancer (cSCC) originating from a burn scar. The burn scar cSCC tends to be more aggressive in nature than conventional skin SCC. treatment of patients with cSCC arising from a burn scar is complicated by the fact that the extensive defects formed after tumor removal are almost impossible to close with local tissues. Purpose: to demonstrate the feasibility of performing surgery for locally advanced cSCC using a thoracodorsal flap. Clinical case description. A 70-year old man presented with cSCC of the right shoulder. The patient had experienced a severe burn covering 70 % of his body surface area at a young age. To repair a large skin defect after tumor resection in the right shoulder, a thoracodorsal artery perforator flap was used. there were no complications in the postoperative period. At a follow-up of 7 months, no evidence of tumor recurrence was observed. Conclusion. The thoracodorsal artery perforator flap has contributed to the efficient reconstruction of extensive soft tissue defects in patients with locally advanced cSCC originating from a burn scar.